Interferência dos aerossóis atmosféricos na precipitação sobre uma região do Cerrado mato-grossense - Brunelli, Thais Costa (2024)
Climate change is a serious problem that the world faces today, and the factors contributing to this change are diverse, one of which is atmospheric aerosol. The impact of aerosols on cloud formation and precipitation is a critical aspect of climate change research. Aerosols can alter the properties of clouds, affecting rainfall patterns. They act as nuclei for cloud droplets, influencing the brightness and reflectivity of these formations. As climate change progresses, understanding these interactions becomes vital for accurately predicting climate patterns. This study focuses on analyzing the indirect effects of aerosols on the climate of the municipality of Cuiabá, Mato Grosso, based on the relationship between aerosol optical depth and precipitation. We utilized data measured by the Aerosol Robotic Network’s sun photometer network, along with precipitation data observed at the surface from the automatic station network of the National Institute of Meteorology. The ability of aerosols to interact with solar radiation in the atmosphere triggers important physical and chemical processes in climate maintenance. By assessing a 20-year period (from January 2000 to December 2020), we observed that the effects of aerosols can lead to a weaker hydrological cycle, reflected in reduced regional rainfall indices. The absorption of solar radiation by aerosols can increase the temperature of the atmospheric boundary layer, leading to thermodynamic stabilization and suppression of convective processes. Depending on the amount of aerosols available in the atmosphere, the solar radiation incident on the surface can be blocked by up to 15% compared to the total incident in a particle-free atmosphere. This reduction in the proportion of solar radiation at the surface limits the photosynthetic process, impacting the flow of matter and energy in ecosystems and reducing the water vapor content in the atmosphere. We conclude that an atmosphere with a high quantity of aerosols causes changes in regional precipitation and, consequently, results in the formation of fewer clouds.